State reproduction through structural power and ideological continuity in Suzanne Collins' Mockingjay - Miftahul Janah; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2025)
In Mockingjay, the fall of the Capitol gives way to a disturbing continuity of power, where the rhetoric of freedom masks familiar forms of control. While District 13 positions itself as the revolutionary alternative, its use of surveillance, propaganda, and authoritarian discipline reflects the very structures it claims to overthrow. This article argues that through Katniss Everdeen’s final act, Suzanne Collins exposes the cyclical nature of state power and the persistence of ideology in legitimizing domination. Drawing on Nicos Poulantzas’s theory of authoritarian statism and the state as a condensation of class struggle, the analysis reveals how the narrative critiques the reproduction of hierarchical structures under the guise of liberation. Rather than celebrating victory, Mockingjay asks whether the revolution truly dismantled power, or simply rebranded it.